Determinants of immunoglobulin G responses to respiratory syncytial virus and rhinovirus in children and adults - Guillien, Alicia; Niespodziana, Katarzyna; Mauclin, Marion; Boudier, Anne; Varraso, Raphäelle; Leynaert, Bénédicte; Dumas, Orianne; Le Moual, Nicole; Schlederer, Thomas; Bajic, Maja; Borochova, Kristina; Errhalt, Peter; et al. (Frontiers in Immunology, 2024)
Introduction: Exposure to respiratory viruses is a significant cause of morbidity and affects virus-specific antibody levels. Little is known about determinants associated with immune response to these viruses. We aimed to investigate the determinants of respiratory syncytial virus (RSV) and rhinovirus (RV) specific IgG responses in both children and adults.The study is based on the EGEA cohort, composed of 530 samples of children in EGEA1 (1991-95) and1241 samples of adults in EGEA2 (2003-07). Cumulative RV-specific IgG responses (species A, B and C) and IgG responses to RSV-G protein were measured by micro-array technology. Multiple linear mixed models (random effect to account for familial dependence) were performed to assess associations between age, sex, body mass index (BMI), tobacco smoke exposure and season of blood sampling with RSV and RV-specific IgG levels. Results: In children (11.1±2.8 years old, 57% of boys), higher RV-specific IgG levels were associated with older age (only for RV-B), female sex and lower BMI, while only older age was associated with higher RSV-specific IgG levels. In adults (43.5±16.7 years old, 48% of men), younger age, female sex, lower BMI, active smoking and all seasons except summer were associated with higher RV-specific IgG levels. Older age, active smoking and all seasons except summer were associated with higher RSV-specific IgG levels. Conclusion: Personal and seasonal determinants of RSV-and RV-specific IgG levels seem to vary according to the respiratory virus type and between children and adults, suggesting different patterns of responses along the life course.